Rethinking Islamic Peace Traditions: A Discourse Analysis of Prophetic Mediation in Conflict Narratives - Ridho, Akhsin; Damairi, Muhammad Uzaer (ADDIN, 2026)
This article reexamines Islamic peace traditions by analyzing how prophetic mediation operates within key conflict narratives. The study responds to the limited theorization of prophetic conflict-resolution practices and the fragmented approaches found in previous works. Using discourse analysis, the research identifies consistent relational, procedural, and normative patterns that reveal an underlying logic in the Prophet's approach to managing disputes. Four significant findings emerge: the systematic under-theorization of prophetic mediation, methodological inconsistencies in earlier studies, recurring narrative structures that sustain interpretive coherence, and the feasibility of formulating a conceptual model grounded in these patterns. The study demonstrates that prophetic mediation is not merely moral guidance but a structured set of conflict-intervention strategies that can inform contemporary peace building. This work advances the field by providing a stronger analytical foundation for developing a practical model of prophetic mediation for modern contexts. The study also opens pathways for future research to operationalize the model and test its applicability across diverse conflict settings.